2019
DOI: 10.1021/acsomega.9b02296
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Sorption to Soilless Media Components Used for Ornamental Plant Production and Aluminum Water Treatment Residuals

Abstract: Commercial producers of containerized ornamental plants almost exclusively use soilless media as the substrate for growing the plants. Soilless media are composed primarily of organic materials as opposed to mineral soils. Significant amounts of pesticides can leach from pots containing soilless media to which pesticides have been added as drenches or top-dressings. One of the goals of this project was to identify whether individual components comprising soilless media have differing affinities for the pestici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The nls­() function of base R was used to perform a nonlinear regression fitting the resulting data to a Freundlich isotherm model, yielding a Freundlich constant ( K F ) of 245 L/kg and exponent of nonlinearity (1/ n ) of 0.751 (Figure SI 9.2). Leiva et al observed K F values of 290.4 and 157.4 L/kg, and 1/ n values of 0.77 and 1 for imidacloprid on peat and pine bark, respectively. Mandal and Singh obtained a K F value of 85.71 L/kg, and a 1/ n value of 0.920 for imidacloprid sorption to eucalyptus bark.…”
Section: Resultsmentioning
confidence: 98%
“…The nls­() function of base R was used to perform a nonlinear regression fitting the resulting data to a Freundlich isotherm model, yielding a Freundlich constant ( K F ) of 245 L/kg and exponent of nonlinearity (1/ n ) of 0.751 (Figure SI 9.2). Leiva et al observed K F values of 290.4 and 157.4 L/kg, and 1/ n values of 0.77 and 1 for imidacloprid on peat and pine bark, respectively. Mandal and Singh obtained a K F value of 85.71 L/kg, and a 1/ n value of 0.920 for imidacloprid sorption to eucalyptus bark.…”
Section: Resultsmentioning
confidence: 98%
“…There is growing evidence that substrate engineering [9] can lead to more sustainable substrates by creating unique physiochemical characteristics [10] to address specific pitfalls in conventional substrates. Recent research has shown that designer or engineered substrates have the potential to reduce weed pressure [11], water use [12], nutrient leaching [13], pesticides leaching [14], and production times [15].…”
Section: Introductionmentioning
confidence: 99%
“…That study identified acephate, a highly water‐soluble pesticide, as having a low affinity (21–31% of pesticide applied) for sorption to most components. The intermediately soluble pesticide imidacloprid had a high affinity for coir, peat, and pine bark, sorbing 76.2–87.1% of the pesticide used in the incubations, whereas paclobutrazol (lowest water solubility of 26 μg L −1 ) showed the highest affinity for pine bark and peat (respectively), with sorption ranging from 88.9 to 92.9% of the total pesticide used in the incubations, and intermediate sorption to coir (70.4%) (Leiva, Wilson, Albano, Nkedi‐Kizza, & O'Conner, 2019). That study illustrates well the fact that media is heterogeneous and the interactions between different chemistries and media components can vary significantly.…”
Section: Discussionmentioning
confidence: 99%